ADOLESCENT’S KNOWLEDGE ABOUT THE RISK OF EARLY MARRIAGE RELATED TO ATTITUDE OF PREVENTING EARLY MARRIAGE IN KECAMATAN PARE KABUPATEN KEDIRI - RATNA FETI WULANDARI; NURIN FAUZIYAH; RATIH KUSUMA WARDHANI (Indonesian Midwifery and Health Sciences Journal, 2023)
Early marriage is a marriage that occur at the age of 18 years old. In 2020, early marriage was 19.26%. The population of women aged 10 years old and over who have ever been married carried out their first marriage at the age of less than 17 years old. The purpose of this study is how the relationship between adolescent’s knowledge about the risk of early marriage and the attitude of efforts to prevent early marriage. The research design method used cross sectional and the measuring instrument was a questionnaire. The independent variable is the knowledge of adolescents about the risk of early marriage while the dependent variable in this study is the attitude of efforts to prevent early marriage. The subjects were teenagers in Kecamatan Pare who had a girlfriend or had been in a relationship. The research sample was 300 respondents and the sampling technique is snowball. Data analysis using Spearman correlation test. The results showed that r = 0.237, sig (p) = 0.000, which means that there is a relationship between adolescent knowledge about the risk of early marriage and the attitude of efforts to prevent early marriage. Keywords: Knowledge, Early Marriage, Attitude, Adolescent